Public-Private Partnership: Understanding the impact of Educational Management Organization model towards the fulfilment of Sustainable Development Goal 4 in the context of Sindh Province of Pakistan. - Sohoo, Muhammed Nawaz; Chandani, Alishah Mukhtar; Abro, Lahoot Tariq; Khoso, Zamir Ahmed; Tagar, Hamzo Khan (Archives of Business Research, 2019)
This paper attempts to develop an understanding regarding the different types of Public-Private Partnership models operating within the education sector of Sindh province of Pakistan and to understand the impact of the Education Management Organizations (EMO) model since its adoption towards the fulfilment of Sustainable Development Goal (SDG) 4. Further on the paper highlights the bottlenecks in the delivery of quality education under the EMO model in of which suggest certain policy recommendations. This study presents insights from personal observation of the authors; a field’s empirical work and another reliable primary data set. It is concluded that it’s a successful model to some extent so it can be imposed with inclusions of philanthropist low-cost model in the entire region for the welfare of humanity and to address the challenge of quality education for all in the region.